Assessment of elementary home economics textbooks in the area of food and nutrition - Lambarte, Sarah Victoria Te; Gabriel, Florenda S. (2008.)
This study evaluated the Home Economics textbooks, from Grades IV to VI, of both public and private elementary schools in the area of food and nutrition. It compared public and private textbooks in terms of physical appearance and book layout, instructional design and organization of material, scope and sequence, and learning competencies. It also determined the usability of the textbooks for the teachers in terms of its quality as a teaching aid, quality as learning tool for students, quality of the learning activities provided, and its alignment with the curriculum. Document analysis of six textbooks from public and private schools in Quezon City was done using checklists adapted from local and foreign textbook evaluation processes. A survey among teachers using the books was done to determine the usability. Results showed that textbooks from public schools were better than those used in private schools in terms of instructional design and organization of the material. The private school textbooks, on the other hand, were better in scope and sequencing of topics and learning competencies set by the DepEd. They were equal in terms of physical layout and book design and in the perceived usability by teachers. Among the six textbooks, Grade VI (private), Grade VI (public), Grade V (public), Grade IV (public) were acceptable based all all the criteria set for evaluation. However, the public school textbooks need major revisions in terms of physical appearance and book layout. Grade IV (private) and Grade V (private) textbooks need major revisions in all the aspects evaluated.
Thesis (BS Home Economics)--University of the Philippines Diliman.
Keywords: Home economics -- Textbooks; Home economics -- Textbooks -- Evaluation